Community structures of bivalves in the coastal area of Lungkap Village, Pinolosian, Bolaang Mongondow Selatan District - Damopolii, Yenita; Kadim, Miftahul Khair; Paramata, Arfiani Rizki (Universitas Malikussaleh, 2024)
This research aims to identify the structure of the bivalve community on the coast of Langkat Village, Pinolosian, South Bolaang Mongondow District. Sampling was carried out from December 2020 to January 2021 at three stations, namely seagrass beds (station I), tourist attractions (Station II), and mangroves (Station III), using the quadrant transect method, where each observation station made a line transect from the mainland towards the sea. Line transects are placed at each station, while the distance between line transects is 50 m. Observation results show that the bivalves at the research location consist of five families (Arcidae, Asteridae, Cyprinidae, Cardiidae, Ostreidae) an six types of bivalves, where the diversity index is low and the uniformity index is moderate, indicating that the distribution of each type is relatively even.Keywords: Bivalve; coastal; community structure; Lungkap